2018
DOI: 10.1108/jbim-10-2016-0237
|View full text |Cite
|
Sign up to set email alerts
|

How brand-oriented strategy affects the financial performance of B2B SMEs

Abstract: Purpose This study aims to examine the relationship between brand orientation and financial performance in business-to-business (B2B) small- and medium-sized enterprises (SMEs). It examines the impact of brand-oriented strategy on financial performance through four branding constructs, namely, internal branding, brand communication, brand awareness and brand credibility. Design/methodology/approach A questionnaire-based survey was conducted to collect data from 250 Finnish B2B SMEs. Confirmatory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 85 publications
(134 reference statements)
4
47
0
3
Order By: Relevance
“…Furthermore, Johansson et al (2012) find that the strength of the relationship between brand equity and financial performance differs according to the measure applied and how each captures the equity. 2 Indeed, there is a scarcity of prior research on the links between brand equity and financial performance, particularly in unlisted firms, even though there is some preliminary research focused on small and medium-sized enterprises (Anees-ur-Rehman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Johansson et al (2012) find that the strength of the relationship between brand equity and financial performance differs according to the measure applied and how each captures the equity. 2 Indeed, there is a scarcity of prior research on the links between brand equity and financial performance, particularly in unlisted firms, even though there is some preliminary research focused on small and medium-sized enterprises (Anees-ur-Rehman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More "integrated" management approaches are, by contrast, characterised by brand-centric management activity, which continually and systematically reflects on the interrelationships between branding, marketing and economic performance (Baumgarth, 2010). Generally, emerging B2B SME research reveals that brandoriented firms have a higher impact on B2B marketing achievement (Mäläskä et al, 2011;Mitchell et al, 2015;Urde et al, 2013;Anees-ur-Rehman et al, 2018).…”
Section: Literature Review 21 Brand Branding and B2b Brand Managementmentioning
confidence: 99%
“…One common SME practice involves imitating and mimicking the branding communication practices of LOs (Spence and Essoussi, 2010). Some research on SME brand communication has found that a firm's interaction with customers is key, as such encounters lead to the spread of Word of Mouth (WOM) communication, and thus generate and disseminate brand awareness (Anees-ur-Rehman et al, 2018;Berthon et al, 2008). In retailing industries, SMEs adopt experiential marketing tools in their approach to brand communication strategy by conceiving of the store environment as a "brand-scape", where interaction between customers and the firm can be designed to inculcate brand awareness through affective customer experience (Hollenbeck et al, 2008;Mitchell et al, 2015).…”
Section: B2b Small and Medium Enterprises Branding Communicationmentioning
confidence: 99%
“…Fifth, Anne Schmitz and Nieves Villaseñor-Román examine the links between brand equity and financial performance in unlisted (unquoted) firms. These authors underline the scarcity of prior research on this issue in this type of firm (Anees-ur-Rehman et al, 2018) and the importance of marketing managers better assigning marketing efforts towards the construction of a brand equity that improves firm profitability. These authors provide evidence that unlisted firms that invest more resources in brand equity have better financial performance, greater earnings persistence and more future profitability.…”
Section: Preface To "Customer Loyalty and Brand Management"mentioning
confidence: 99%